2017
DOI: 10.1016/j.jallcom.2016.08.211
|View full text |Cite
|
Sign up to set email alerts
|

Study of the photocatalytic activity of Fe3+, Cr3+, La3+ and Eu3+ single-doped and co-doped TiO2 catalysts produced by aqueous sol-gel processing

Abstract: An aqueous sol-gel process, previously developed for producing undoped and Cu 2+ , Ni 2+ , Zn 2+ or Pb 2+ doped TiO 2 photocatalystswith remarkably high photocatalytic activity without requiring any calcination step, has been adapted to produce Fe 3+ , Cr 3+ , La 3+ or Eu 3+ singledoped TiO 2 photocatalysts as well as La 3+-Fe 3+ and Eu 3+-Fe 3+ co-doped TiO 2 catalysts. The physicochemical properties of the obtained catalysts have been characterized using a suite of complementary techniques, including ICP-AES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 45 publications
1
29
0
2
Order By: Relevance
“…Analyzing the values obtained in relation to the nominal metallic load of Fe, it was observed that the band gap is likely to decrease with an increase in the Fe quantity. This also happens with samples of iron-doped TiO 2 catalysts [30,31]. It obtained the following values for the calcination temperature at 673 K (0.5% Fe-4.75 eV and 1.5% Fe-3.28 eV).…”
Section: Photoacoustic Spectroscopy (Pas)mentioning
confidence: 54%
See 1 more Smart Citation
“…Analyzing the values obtained in relation to the nominal metallic load of Fe, it was observed that the band gap is likely to decrease with an increase in the Fe quantity. This also happens with samples of iron-doped TiO 2 catalysts [30,31]. It obtained the following values for the calcination temperature at 673 K (0.5% Fe-4.75 eV and 1.5% Fe-3.28 eV).…”
Section: Photoacoustic Spectroscopy (Pas)mentioning
confidence: 54%
“…Afterward, it was then calcined at different temperatures (633, 673, 773, 873, and 913 K) with heating ramps. (ii) Catalytic immobilization-for the catalyst immobilization, it used a methodology adapted from Reference [31], which incorporated sodium alginate as the polymer matrix. The concentrations used were: sodium alginate 2% (w/v) and photocatalyst 1g L −1 .…”
Section: Fe/nb 2 O 5 Immobilized Synthesismentioning
confidence: 99%
“…The absorbance spectra were transformed using the Kubelka-Munk function [10,64,65] to produce a signal, normalized for comparison between samples, and so to calculated the band gaps (Eg,direct and Eg,indirect). The details of this treatment method have been widely described elsewhere [53,54,66].…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Besides, TiO 2 modication by metal ion doping has also been extensively studied. [20][21][22][23][24] Wu et al 25 synthesized Cu-doped TiO 2 by hydrothermal synthesis and air heat treatment. 0.5 mol%-Cu/TiO 2 shows better photocatalytic activity than pure TiO 2 because it enlarges the visible light absorbance due to the presence of Cu 3d orbitals.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some studies have shown that single element displays better modication effect than multi-elements. 24,29 Khan et al's research 29 indicates that Ga-doped TiO 2 exhibits better photocatalytic performance than N/Ga co-doped TiO 2 . Malengreaux et al 24 reported that Eu/Fe co-doped TiO 2 shows lower photocatalytic efficiency than Fedoped TiO 2 and pure TiO 2 .…”
Section: Introductionmentioning
confidence: 99%